Children of war, children of hope - AsiaVisions Media Foundation; Gabriela (Organization : Manila, Philippines).; LC Purchase Collection (Library of Congress) ([Quezon City] Asia Visions Media Foundation, 1989)
Features the Gabriela-initiated campaign called Children support children victims of war, against militarization and human rights violations on children in the Philippines.
Also issued on videocassette.
Chiefly in English, some dialogue also in Tagalog.